STANDARD KENYAMANAN KERJA DI DALAM RUANG UNTUK PENINGKATAN PRODUKTIVITAS - Pamudji Suptandar (Jurnal Dimensi Seni Rupa dan Desain, 2003)
Abstract The suitable at work's place are the demands for every person due to the working atmosphere is suitable , quite, peaceful and comfortable will bring joy and happiness. Contrary to those demands, thus there should be standard wich will be the basic guidance for architrcts and interior designer in order for them to increase interior productivity and effectively at work